Sustainable development goal 5: How does the Philippines fare on gender equality? - Clarissa C. David; Jose Ramon G. Albert; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2018)
The global goal to attain gender equality, including ending all forms of discrimination against women and girls, and ensuring their safety, is central to the achievement of the Sustainable Development Goals. Its attainment means that every person, regardless of sex, is empowered to reach their full potential. This entails having both men and women given equal opportunities to education, paid employment, and real decisionmaking power whether in private or public sectors. This paper discusses how the country fares in several gender-related indicators that can be used to monitor progress toward gender equality and women empowerment. It provides an overview of the current situation in areas such as equality of human capabilities, equality of economic opportunity, equality in political voice and leadership, and the safety of women and girls. The paper also identifies priorities for public policy while seeking new directions in addressing several transformational issues to attain gender equality and women empowerment in the country.
Keywords: 330; decentralization; expenditure assignment; equalization transfers; federal government; fiscal autonomy; intergovernmental transfers; political dynasties; political turncoatism; tax assignment; unitary government; vertical fiscal gap; vertical fiscal imbalance